K Deprivation Modulates the Primary Metabolites and Increases Putrescine Concentration in Brassica napus - Réthoré, Elise; Jing, Lun; Ali, Nusrat; Yvin, Jean-Claude; Pluchon, Sylvain; Hosseini, Seyed Abdollah (Frontiers in Plant Science, 2021)
Potassium (K) plays a crucial role in plant growth and development and is involved in different physiological and biochemical functions in plants. B. napus needs higher amount of nutrients like nitrogen (N), K, phosphorus (P), sulfur (S), and boron than cereal crops. Previous studies in B. napus are mainly focused on the role of N and S or combined deficiencies. Hence, little is known about the response of B. napus to K deficiency. Here, a physiological, biochemical, and molecular analysis let to investigate the response of hydroponically grown B. napus plants to K deficiency. The results showed that B. napus was highly sensitive to the lack of K. The lower uptake and translocation of K induced BnHAK5 expression and significantly declined the growth of B. napus after 14 days of K starvation. The lower availability of K was associated with a decrease in the concentration of both S and N and modulated the genes involved in their uptake and transport. In addition, the lack of K induced an increase in Ca2+ and Mg2+ concentration which led partially to positive charge accumulation. Moreover, a decrease in the level of arginine as positively charged amino acid was observed which was correlated with a substantial increase in polyamine putrescine. Furthermore, K deficiency induced the expression of BnNCED3 as key gene in ABA biosynthetic pathway which was associated with an increase in the levels of ABA. Our findings provided a better understanding of the response of B. napus to K starvation and will be useful for considering the importance of K nutrition in this crop.